KURANG ASUPAN VITAMIN A, C, E DAN BETA KAROTEN MENINGKATKAN KEJADIAN PREEKLAMPSIA DI RSUP DR. SARDJITO, YOGYAKARTA - Nofrisa Mutia P; T. Ninuk Sri Hartini; Mohammad Hakimi (GIZI INDONESIA, 2010)
The Objective of this study was to evaluate the vitamin A, C, E and beta carotene intakes and preeclampsia among pregnant women. The data were analyzed from 30 pregnant women with preeclampsia as a case group and 30 healthy pregnant women as a control group. The survey was carried out between July 2004 and February 2005 at Sardjito Hospital, Yogyakarta. The nutrient intakes are presented as median values and the Kruskal- Wallis test and the Mann-Whitney U test were used. Multiple linear regression models were used to examine the factors associated with preeclampsi a. In total, 23 percent pregnant women craved foods, 40 percent avoided certain foods, 23 percent had consumed jamuduring pregnancy and 68% were consuming iron supplements. The percentage of healthy pregnant women consumed iron supplements was higher than pregnant women with preeclampsia (p0.05). In contrast, the percentage of healthy pregnant women consumed jamu was lower than pregnant women with preeclampsia (p0.05). Healthy pregnant women had higher vitamin A, C, E and beta carotene intakes than pregnant women with preeclampsia. There were no significant differences among those groups. Pregnant women consuming low vitamin A, C, E and beta carotene intake are at risk of developing preeclampsia.Keywords: pregnant women, preeclampsia, vitamin A, C, E and beta carotene intake